What constitutes a compensation free regulation of foreign-owned property in international law? Some thoughts on the protection of foreign investment against expropriations, the states' right to regulate, arbitrators and TTIP - Rainer Gildeggen; Andreas Willburger (Hochschule Pforzheim, 2016)
This article intends to help understand the debate about TTIP by focusing on the specific issue of how TTIP may regulate investment protection of foreign-owned property. It gives an overview of the international law of expropriations of and other interferences with foreign-owned property for public welfare objectives such as public health and safety, environmental protection, public morals, the promotion and protection of cultural diversity and human rights, and asks whether such interferences require the payment of compensation. It also describes the role arbitrators played in the development of the international law concerning the taking of foreign-owned property. With this legal background in mind it elaborates that TTIP investment protection rules and dispute settlement provisions may be an indicator on what TTIP really is: an instrument for the benefit of the citizens in Europe and the United States or a means to outplace national interests and democracy in favor of multinational enterprises. The article expresses the hope that the protection of foreign-owned property will not be regulated in the TTIP agreement and that the settlement of investment disputes between investors and states will not be put into the hands of arbitrators but of the judges of the country where the taking took place.
urn:nbn:de:bsz:951-opus-279
Keywords: 330; investment protection; expropriation; right to regulate; international law; arbitration; TTIP